A Report on Project Phase-2 Message and Power Management in Military Applications - PAVAN KUMAR D S (2009)
INTERNAL GUIDE:SREEDEVI N,MVJCE EXTERNAL GUIDE:SHAMBHULING R DODDAMANI,CAIR
Keywords: Power Management in Military Applications